Software defined access networks - Maricato, José Miguel Duarte (2016)
With the increase of internet usage and the exponential growth of bandwidth consumption due to the increasing number of users of new generation equipments and the creation of new services that consume increasingly higher bandwidths, it's necessary to nd solutions to meet these new requirements. Passive optical networks (PONs) promise to solve these problems by providing a better service to users and providers. PON networks are very attractive since they don't depend on active elements between their end points, leading to lower maintenance costs and better operational e ciency. PON technologies addressed in this dissertation are the G-PON (Gigabit PON), currently standardized and implemented in access networks across the world, and the NG-PON2 (Next-Generation PON 2), which is the next step on access networks evolution and is currently on the process of study and standardization. The NG-PON2 must co-exist on the same optical distribution network of the G-PON, so it re-utilizes the already built infrastructures and consequently protect providers initial investment. Software De ned Networks (SDN) is an emerging architecture that decouples network control and forwarding functions from the hardware they belong, making possible for network control to be programmable, enabling the implementation of solutions capable of solving the increasing complexity of the networks problem and the creation of innovative services. The study main focus is the SDN as an enabling mechanism for network elements virtualization. In this dissertation is studied the G-PON and NG-PON2 architectures in the context of the ITU-T G.984.x and G.989.x recommendations respectively, and the study of the SDN technology through documentation available online. And based on the studies made it's going to be proposed a server architecture that enables the control of G-PON and NG-PON2 infrastructure elements, introducing virtualization SDN concepts on access networks.